I, Robot (Robot, ,, 2006)
This classic science fiction masterwork by Isaac Asimov weaves stories about robots, humanity, and the deep questions of existence into a novel of shocking intelligence and heart.   “A must-read for science-fiction buffs and literature enjoyers alike.”—The Guardian I, Robot, the first and most widely read book in Asimov’s Robot series, forever changed the world’s perception of artificial intelligence. Here are stories of robots gone mad, of mind-reading robots, and robots with a sense of humor. Of robot politicians, and robots who secretly run the world—all told with the dramatic blend of science fact and science fiction that has become Asimov’s trademark.  The Three Laws of Robotics: 1) A robot may not injure a human being or, through inaction, allow a human being to come to harm. 2) A robot must obey orders given to it by human beings except where such orders would conflict with the First Law. 3) A robot must protect its own existence as long as such protection does not conflict with the First or Second Law. With these three, simple directives, Isaac Asimov formulated the laws governing robots’ behavior. In I, Robot, Asimov chronicles the development of the robot from its primitive origins in the present to its ultimate perfection in the not-so-distant future—a  future in which humanity itself may be rendered obsolete. “Tremendously exciting and entertaining . . . Asimov dramatizes an interesting question: How can we live with machines that, generation by generation, grow more intelligent than their creators and not eventually clash with our own invention?”—The Chicago Tribune

House of robots (House of robots, 1,, 2014)
"Fifth-grader Sammy Hayes-Rodriguez struggles to fit in when his inventor mother requires him to take her latest creation, a robotic 'brother,' to school with him to learn to become a student"--

Robots go wild! (House of robots, 2,, 2015)
"Fifth grader Sammy Hayes-Rodriguez has to find a solution when his robot 'brother' has repeated malfunctions at school and a newer model robot steps in as competition--and his mother's job is in jeopardy as a result"--

Robot revolution (House of robots, 3,, 2017)
"Robots on strike! Sammy's underappreciated mechanical helpers cause chaos in the house! It's up to Sammy and his disabled sister Maddie to keep the peace until his inventor mom reveals her secret project...and why it was worth the wait"--

Flying robots (Blastoff! discovery. World of robots, ,, 2018)
"Engaging images accompany information about flying robots. The combination of high-interest subject matter and narrative text is intended for students in grades 3 through 8"--
Flying robot at work! , What are flying robots? , Development of flying robots , Profile of flying robot : Camcopter S-100 , Profile of flying robot : Skunk , Profile of flying robot : MQ-1 Predator , Profile of flying robot : M2 drone , Future of flying robots.

Medical robots (Blastoff! discovery. World of robots, ,, 2018)
"Engaging images accompany information about medical robots. The combination of high-interest subject matter and narrative text is intended for students in grades 3 through 8"--
Medical robot at work! , What are medical robots? , Development of medical robots , Profile of medical robot: Da Vinci , Profile of medical robot: Robear/Riba , Profile of medical robot: Riva , Profile of medical robot: Robot Rx , Future of medical robots.

Military robots (Blastoff! discovery world of robots, ,, 2018)
"Engaging images accompany information about military robots. The combination of high-interest subject matter and narrative text is intended for students in grades 3 through 8"--
What are military robots? , Development of military robots , Profile of military robot: Packbot , Profile of military robot: Bigdog , Profile of military robot: Robart III , Profile of military robot: Talon , Future of military robots , Glossary.